(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The article speaks about research projects of Ancient Topography Chair of State University in Milan since 2005 to 2008.In each of them, has been applied survey to improve archaeological data, both in Landscape Archaeology Project “Paesaggi d’Acqua” in Orbetello’s lagoon (Tuscany), both in topographical surveys along east riverside of Lario and in Friuli Highland, near Pordenone.In last two cases, surveys projects got to excavation of single archaeological contexts: a roman villa near Maniago (PN) and an Early medieval fort near Lecco (CO). So we could better understand the development of human network in each area and the chronological growth of the territory.